The relationship between push and pull factors and intention to visit muslim-friendly hospitals for medical tourism among Malaysian Muslim consumers - Soban, Rizq Nadiah; Abu Bakar, Elistina; Md. Jusoh, Zuroni (Malaysian of Consumer And Family Economics Assosiation, 2022)
Muslim-friendly medical tourism holds great potential in assisting with the post-covid efforts for the country. As of current literature, there is no prior research on what drives Malaysian Muslim consumers to visit Muslim-friendly hospitals. This study proposed the effects of push and pull factors on the intention to visit Muslim-friendly hospitals for medical tourism. A structured questionnaire was designed and distributed to 400 respondents who were sampled through multistage random sampling throughout the five zones in Malaysia; North Zone, East Zone, West Zone, South Zone, and Borneo Zone. Multiple regression analysis was used to analyse the data in order to examine the relationship between the push factors (religiosity and novelty-seeking), pull factors (Islamic attributes of hospitals) and the intention to visit Muslimfriendly hospitals for medical tourism. The result of the analysis indicated that religiosity and Islamic hospital attributes are the main push and pull factors that respectively predict the consumer’s intention to visit Muslim-friendly hospitals for medical tourism. Novelty-seeking, however, was found to not be able to predict the intention. This study can serve as a framework to enhance Malaysia’s Muslim-friendly hospitals to cater to medical tourists, both locally and internationally. The findings of this research can also contribute to the government and industry players in their post-COVID efforts to revive the local medical tourism industry and subsequently boost the Malaysian economy.